Collaboration of Islamic Values and Local Wisdom in Communal Economic - Umah, Khurul Aimmatul; Sa'idaturrohmah, Nur (Proceedings of Annual Conference for Muslim Scholars, 2024)
The collaboration between Islamic values and local wisdom in communal economic management has the potential to create strong synergy in improving welfare and maintaining social harmony. This study aims to analyze this collaboration within the context of the multicultural society in Balun Village, Turi, Lamongan, known as the "Village of Tolerance," where various religions coexist harmoniously. Using a Qualitative approach with a library study method, the research explores the role of Islamic values such as justice, balance, and mutual cooperation (gotong royong), as well as local wisdom, in fostering harmony and ensuring the sustainability of communal economics. The findings indicate that the integration of Islamic values with local practices strengthens social solidarity, enhances religious tolerance, and maintains economic balance and sustainability. This collaboration demonstrates that spiritual values and local traditions can serve as a critical foundation for building an inclusive and just economic system.